Clinical outcomes of transcatheter aortic valve replacement stratified by left ventricular ejection fraction: A single centre pilot study. (May 2022) - Al Balool, Joud; Al Jarallah, Mohammed; Rajan, Rajesh; Dashti, Raja; Alasousi, Nader; Kotevski, Vladimir; Taha Mousa, Ahmed Said; Al Haroun, Retaj; Tse, Gary; Zhanna, Kobalava D.; Setiya, Parul; Saber, Ahmad Al; et al.
Abstract: Introduction: To define baseline echocardiographic, electrocardiographic (ECG) and computed tomographic (CT) findings of patients with heart failure undergoing transcatheter aortic valve replacement (TAVR) and analyze their overall procedural outcomes. Methods: Between 2018 and 2021, patients with severe aortic stenosis (AS) who performed transcatheter aortic valve replacement (TAVR) in Sabah Al Ahmad Cardiac Centre, Al Amiri Hospital were identified. A retrospective review of patients' parameters including pre-, intra-, and post-procedural data was conducted. Patients were grouped in 2 subgroups according to their EF: EF <40% (HFrEF) and EF ≥ 40%. The data included patients' baseline characteristics, electrocardiographic and echocardiographic details along with pre-procedural CT assessment of aortic valve dimensions. Primary outcomes including post-operative disturbances, pacemaker implantation and in-hospital mortality following TAVR were additionally analyzed. Results: A total of 61 patients with severe AS underwent TAVR. The mean age was 73.5 ± 9, and 21 (34%) of the patients were males. The mean ejection fraction (EF) was 55.5 ± 9.7%. Of 61 patients, 12 (20%) were identified as heart failure with reduced EF (<40%). These patients were younger, more often males, and were more likely to have coronary artery disease (75% versus 53.1%). Left ventricular hypertrophy and diastolic dysfunction was documented in 75% and 58.3% of patients with heart failure with reduced ejection fraction (HFrEF) respectively. Post TAVR conduction disturbances, with the commonest being LBBB was observed in 41.7%. Permanent pacemaker was implanted in 3 of patients with HFrEF (25%). There were no significant differences between the two groups with regards to in hospital mortality (p = 0.618). Conclusion: Severe AS with EF <40% constitute a remarkable proportion of patients undergoing TAVR. Preliminary results of post-operative conduction disturbances and in hospital mortality in HFrEF patients were concluded to not differ from patients with LVEF ≥40%. Highlights: This is the first reported outcome study of TAVR in patients with heart failure in Kuwait. Conduction disturbances induced by TAVR was observed in almost half of the patients. Systolic dysfunction was not a predictor of in hospital complications or mortality outcomes.